Under Italian Eyes: L’adattamento televisivo italiano di The Secret Agent e gli spettri del terrorismo (Altre Modernità, 2019)
Joseph Conrad’s The Secret Agent (1907) is a novel that reflects Conrad’sambivalent poetics and allusive style. In this text, psychological analysis does not simplyrepresent the background of the story, but its narrative matrix. However, despite thefact that The Secret Agent would seem, apparently, to be unsuitable for visualadaptation, there have been various TV and cinema translations.Our investigation will prove the novel’s capacity to “adapt” to different historical andcultural contexts. After a brief introduction to other screen afterlives of Conrad’s novel,starting with Alfred Hitchcock’s Sabotage (1936), we will focus on a TV adaptationbroadcast on Italy’s national network RAI in 1978. Directed by Antonio Calenda (scriptby Dante Guardamagna and Franco Vegliani), L’agente segreto was produced in the socalled“Years of Lead” and when the “Strategy of Tension” was at its peak. In this respect,this TV version addressed issues that were cogent during the late-seventies in Italy.Moreover, it is significant that Dante Guardamagna also directed, in the same year, theTV adaptation of Ferdinando Camon’s novel Occidente (1975), which investigated thepsyche of a right-wing terrorist.